KESULITAN BERPIKIR ABSTRAK MATEMATIKA SISWA DALAM PEMBELAJARAN PROBLEM POSING BERKELOMPOK - Iik Nurhikmayati (KALAMATIKA Jurnal Pendidikan Matematika, 2017)
This study based on the difficulty of students to think abstractly in the material geometry. There are still many students who feel confused when should imagine and then describe each object geometry because basically a lot of material geometry using visualization mathematical model that concretely not real and do not always exist in everyday life. The difficulties caused students cannot resolve the problems on the material geometry. This illustrates the poor ability of students' mathematical abstraction. One of the methods that can improve the ability of mathematical abstraction is a problem posing learning groups. The purpose of this study is (1) to describe the difficulty of students of abstract mathematical thinking in problem posing learning groups; (2) determine the factors that cause difficulty in abstract mathematical thinking in problem posing learning groups. This study used a qualitative research approach and descriptive. The subjects of this study are students of class X IPA 1 SMAN 1 Leuwimunding Leuwimunding 2015/2016 totaling 36 students. The instrument used in this study is a matter of mathematical abstraction ability tests, questionnaires and interview guidelines. The results showed there are still many students who have difficulty in abstract mathematical thinking in problem posing learning groups which are (1) students lack mastery of concepts; (2) the student does not perform direct experience with the object; (3) students are less able to apply the concept in an appropriate context; and (4) students have difficulty in manipulating abstract mathematical object. While the factors that lead to difficult students to think abstractly derived from external factors, namely the lack of media use props in learning